Ergonomic Environmental Relations with Occurrence of Work Accidents in Hisara Bali Garment Factory Garment Workers - Biomi, Agnes Ayu; Prihastini, Komang Angga; Swandewi, Ni Putu Diana (Public Health and Safety International Journal, 2023)
Industrialization in Indonesia supports the use of technology, equipment, machines and various materials to produce good products or services in order to compete in the market. However, along with these progress and developments, it triggers various Occupational Safety and Health (K3) problems, such as increasing sources of danger, increasing potential hazards, risk of illness and accidents due to work. So this research was conducted to obtain the relationship between the ergonomics environment and the occurrence of work accidents in garment workers at Hisara Bali Garment Factory. The design of this research is descriptive qualitative research. The sample of this research is all garment workers at Hisara Bali Garment Factory, totaling 25 people because it uses total sampling. Data was collected by giving questionnaires and data analysis was done by Univariate analysis and Bivariate analysis using Chi-Square test. The results showed that there is a relationship between the ergonomics environment and the occurrence of work accidents, so it is necessary to improve the ergonomic environment in order to minimize the occurrence of work accidents at Hisara Bali Garment Factory.